Randomized controlled trial of ionization and photoelectric smoke alarm functionality. Issue 2 (3rd April 2008) - Mueller, B A; Sidman, E A; Alter, H; Perkins, R; Grossman, D C
Abstract : Objective: To compare functionality, reasons for non-function, and nuisance alarm levels of two common types of smoke alarms after installation in low- to mid-level income households in King County, Washington. Methods: Randomized controlled trial of 761 households. An ionization or photoelectric smoke alarm was installed between June 1, 2000 and July 31, 2002. Main outcome measures were: percentage of study alarms that were working, observed reasons for non-functional status, and self-reported frequency of nuisance alarms at 9 and 15 months of follow-up. Results: At 9 months after installation, 20% of ionization, vs 5% of photoelectric alarms were non-functional, a difference that persisted at 15 months, with the most common reasons for both types being a disconnected or absent battery. The risk ratio for ionization, relative to photoelectric alarms, being non-functional or removed was 2.7 (95% CI 1.8 to 4.1) at 15 months of follow-up. These findings were not altered by educational level, or the presence of smokers, children <5 years, or adults ⩾65 years. Conclusions: Burn prevention efforts are geared towards increasing smoke alarm ownership and improving maintenance of functional status. Results suggest that the selective use of photoelectric alarms by fire injury prevention programs or consumers may provide longer-term protection in similar populations. Designing smoke alarms that minimize nuisance alarming may also result in longer term functionality.